Bilateral diplomacy : the perspective of a small state understanding, acting, succeeding in international relations in the twenty-first century - Miles, Cheryl ([CCS] [Georgetown]GY, 2009)
Examines the role of bilateral diplomacy and provides a brief overview of the author's work in post.